Analisis Hubungan antara Pendapatan, Dana Pihak Ketiga, dan Return On Asset dengan Tingkat Bagi Hasil Deposito Mudharabah - Ali, Haedar; Supriyanto, Supriyanto (Journal of Finance and Islamic Banking, 2018)
The income, DPK (Third Party Funds), ROA (Return on Assets), and profit-sharing rate of mudharabah deposits constitute essential components of a bank's balance sheet, with hypothesized interrelations. Understanding these relationships is crucial for informing managerial decision-making processes. This study seeks to meticulously examine the potential correlations between income, DPK, and ROA with the profit-sharing rate of mudharabah deposits. The dataset utilized comprises BNI Sharia's quarterly reports spanning the years 2010 to 2015. Pearson's correlation was employed for data analysis. The findings of this study indicate a significant relationship between income and the profit-sharing rate of mudharabah deposits. However, no such relationship was observed between DPK and ROA with the profit-sharing rate of mudharabah deposits. This research makes noteworthy contributions: firstly, to academia by providing empirical evidence supporting existing theories; and secondly, to bank managers by furnishing valuable insights that can aid in making informed decisions.